A definition of catheter-related infection - Bach, Alfons (Zentralblatt für Bakteriologie, 1995)
There is controversy about the definitions of catheter-related infection. The term “infection” implies a physiological reaction by the patient to a pathogenic microorganism. However, the organism has no pathognomonic infectious reaction to a colonised catheter, with the exception of a local exit-site infection. Therefore, suggestions have been made that the definition of catheter-related infection should be based solely on the degree of bacterial colonisation, i. e. the number of colony forming units recovered from the catheter. Although this method does not define catheter-related infections in the strict sense, the approach may be useful for comparing various studies carried out on this topic. However, various methods are used to analyse intraluminal and/or extraluminal colonisation, and comparison of data across studies is difficult. Ideally studies addressing this issue should use a combination of different methods to analyse catheter colonisation. On the basis of microbiological semi-quantitative or quantitative analysis of bacterial colonisation, an attempt should be made to correlate the clinical symptoms of infection to these culture results in order to define useful cutoff values.